A STEM Experiential Learning Experience : A Five-Year Synthesis of Lessons Learned - McCarthy , Deborah L. (Experiential Learning and Teaching in Higher Education, 2022)
From Fall 2012 to Fall 2016, 127 teacher candidates at a public university in southern Louisiana and elementary school students in grades four, five, six, and eight formed a Science, Technology, Engineering, and Mathematics (STEM) partnership to develop and implement science projects. The research questions of the accompanying study over the five years were: 1.Will mentoring a science project increase student understanding of best practices afforded by the scientific method? 2. What strategies improve the quality of a STEM experiential learning experience? A paired-samples t-test on teacher candidates’ pre- and post-test scores showed a significant difference in mean scores, indicating an increase in understanding in students for each of the five years. Themes emerging from the qualitative data suggest that successful strategies include preparation, staying small, organization, communication, motivation, and acknowledgement. Coincidentally, these themes closely mirror the National Society for Experiential Education’s (NSEE) “Eight Principles of Good Practice for All Experiential Learning Activities.”